Characterization of the [3Fe–4S]0/1+ cluster from the D14C variant of Pyrococcus furiosus ferredoxin via combined NRVS and DFT analyses. Issue 17 (11th April 2016) - Lauterbach, Lars; Gee, Leland B.; Pelmenschikov, Vladimir; Jenney, Francis E.; Kamali, Saeed; Yoda, Yoshitaka; Adams, Michael W. W.; Cramer, Stephen P.
Abstract : A combined NRVS and DFT approach to characterize the redox-dependent vibrational properties of a [3Fe–4S] 0/1+ cluster. Abstract : The D14C variant of Pyrococcus furiosus ferredoxin provides an extraordinary framework to investigate a [3Fe–4S] cluster at two oxidation levels and compare the results to its physiologic [4Fe–4S] counterpart in the very same protein. Our spectroscopic and computational study reveals vibrational property changes related to the electronic and structural aspects of both Fe–S clusters.